A facile synthesis and fungicidal activities of 2-(alkylamino)-5,6-dimethylthieno[2,3-d]pyrimidin-4(3H)-ones - Hu, Yang-Gen; Zheng, Ai-Hua; Ruan, Xu-Zhi; Ding, Ming-Wu (Beilstein Journal of Organic Chemistry, 2008)
The aza-Wittig reactions of iminophosphorane 3 with aromatic isocyanates generated carbodiimides 4, which were reacted with alkylamines under mild conditions to give a series of 2-(alkylamino)-5,6-dimethylthieno[2,3-d]pyrimidin-4(3H)-ones 6 and 8 in satisfactory yield. Their structures were confirmed by 1H NMR, EI-MS, IR and elementary analysis, and compound 8c was further analyzed by single-crystal X-ray diffraction. The preliminary bioassays indicated that these compounds showed excellent fungicidal activities against six kinds of fungi.
Keywords: 2-(alkylamino)-5,6-dimethylthieno[2,3-d]pyrimidin-4(3H)-one; aza-Wittig reaction; fungicidal activity; synthesis